2022
DOI: 10.1093/eurpub/ckac031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on contact tracing of patients with pulmonary tuberculosis

Abstract: Background The COVID-19 pandemic could have negative effects on tuberculosis (TB) control. The objective was to assess the impact of the pandemic in contact tracing and latent tuberculosis infection (LTBI) in contacts of patients with pulmonary TB in Catalonia (Spain). Methods Contact tracing was carried out in cases of pulmonary TB detected during 14 months in the prepandemic period (1/1/2019 to 28/2/2020) and 14 months in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“… 26 On the other hand, articles revealed that there was an increase in the proportion of LTBI among TB contacts during the pandemic, which ranged from 5.9% to 14.3% difference. 27 28 This trend was more prominent in children as observed through a much higher percentage of LTBI and active TB among children who were household contacts in 2020 compared to 2019 (57.7% vs. 5.3%) 29 and less than 30% of TB preventive treatment rate among children under the age of 5 years. 2 30 …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“… 26 On the other hand, articles revealed that there was an increase in the proportion of LTBI among TB contacts during the pandemic, which ranged from 5.9% to 14.3% difference. 27 28 This trend was more prominent in children as observed through a much higher percentage of LTBI and active TB among children who were household contacts in 2020 compared to 2019 (57.7% vs. 5.3%) 29 and less than 30% of TB preventive treatment rate among children under the age of 5 years. 2 30 …”
Section: Resultsmentioning
confidence: 97%
“…Like TB testing and screening programs, TB case finding and contact tracing has been impacted by the pandemic, from full suspension of activities in Indonesia to a limited and/or less exhaustive operation in India, China, and Spain. 27 42 43 44 A single country study in Spain suggested that the limited operation of active case finding and contact tracing amidst COVID-19 might have led to increased transmission within households. 27 TB contact tracing is recognized as a labor-intensive process and numerous studies suggested incorporating digital health technologies in its process to promote efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations